2012
DOI: 10.1007/s00259-012-2237-2
|View full text |Cite
|
Sign up to set email alerts
|

A European multicentre PET study of fibrillar amyloid in Alzheimer’s disease

Abstract: PurposeAmyloid PET tracers have been developed for in vivo detection of brain fibrillar amyloid deposition in Alzheimer’s disease (AD). To serve as an early biomarker in AD the amyloid PET tracers need to be analysed in multicentre clinical studies.MethodsIn this study 238 [11C]Pittsburgh compound-B (PIB) datasets from five different European centres were pooled. Of these 238 datasets, 18 were excluded, leaving [11C]PIB datasets from 97 patients with clinically diagnosed AD (mean age 69 ± 8 years), 72 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(135 citation statements)
references
References 41 publications
11
117
0
7
Order By: Relevance
“…Furthermore, amyloidimaging alone may not be helpful with regard to distinguishing between amyloid-positive subtypes of AD (typical AD, logopenic variant of progressive aphasia, and posterior cortical atrophy) [261]. With regard to early diagnosis, a number of studies demonstrated a high predictive value of a positive amyloid-scan in the stage of MCI with regard to conversion to AD [275,276]. Even in subjects with subjective memory impairment, increased levels of amyloid deposition have been described [277] and Reiman et al (2009) were able to demonstrate elevated amyloid-levels in asymptomatic carriers of the APOE e4 allele [278].…”
Section: Amyloid-pet Imagingmentioning
confidence: 99%
“…Furthermore, amyloidimaging alone may not be helpful with regard to distinguishing between amyloid-positive subtypes of AD (typical AD, logopenic variant of progressive aphasia, and posterior cortical atrophy) [261]. With regard to early diagnosis, a number of studies demonstrated a high predictive value of a positive amyloid-scan in the stage of MCI with regard to conversion to AD [275,276]. Even in subjects with subjective memory impairment, increased levels of amyloid deposition have been described [277] and Reiman et al (2009) were able to demonstrate elevated amyloid-levels in asymptomatic carriers of the APOE e4 allele [278].…”
Section: Amyloid-pet Imagingmentioning
confidence: 99%
“…Indeed, we know that while amyloid negativity has an excellent negative predictive value for conversion [21,22], among amyloid-positive MCI subjects, the interval to progression can be variable, and functional measures can predict more accurately the time to conversion [23,24]. Although the value of FDG PET in this setting is well established, perfusion measures should be validated for this specific and highly interesting indication [25][26][27][28].…”
mentioning
confidence: 99%
“…Subsequently many studies have replicated this finding [3][4][5][6][7]. Also, a substantial number of papers on [ 11 C]PiB PET have been published in the European Journal of Nuclear Medicine and Molecular Imaging, which underscores the recognition of the importance of this topic by the Editorial Board of our Journal [8][9][10][11]. Importantly, several studies confirmed that the in vivo observations with [ 11 C]PiB PET are highly correlated with post-mortem assessment of amyloid pathology [12][13][14] [21,22].…”
mentioning
confidence: 68%